P98 A decade of primary tumours of the spine in the paediatric population. Issue 3 (14th February 2019) - Millward, CP; Foster, M; Tonder, LV; Williams, D; Pizer, B; Pettorini, B; Parks, C; Mallucci, C
Abstract : Objectives: Primary spinal tumours in children are rare and poorly understood; we review 10 years of surgical experience. Design: Retrospective review of prospectively maintained database. Subjects: Children receiving surgical management of primary spinal tumours in a single, tertiary paediatric neurosurgery centre. Methods: Operations for primary spinal tumours were abstracted from our prospectively maintained surgical database and supplemented with data from case notes, operative records, and imaging studies. Results: Between 2008 and 2017, 37 procedures were performed on 29 patients (19 male; Median age 7.5 years, IQR 2–11.25). 28 had their primary procedure in our unit: 21 excisions, and 7 biopsies (of which 5 proceeded to further surgery). Tumours were classified as extradural (10), intradural extramedullary (3), intradural intramedullary (11) or bony (4). Tumours were found at the following levels: Cervical (8; 29%), Cervicothoracic (2; 7.1%), Thoracic (10; 36%), Thoracolumbar (3; 11%), Lumbar (2; 7.1%), Lumbosacral (2; 7.1%) and Sacral (1; 3.6%). Histology comprised: Pilocytic Astrocytoma (6), Other Astrocytoma (4), Schwannoma (3), Ewing Sarcoma (2), Langerhans cell histiocytosis (2), Lymphoma (2), Neurofibroma (2), and others (7) including one Myxopapillary Ependymoma. Conclusions: The rarity and heterogeneity of paediatric spinal tumours makes treatment challenging. We propose a national online registry including a tissue bank, and invite collaboration with other units.